A reassessment of the enigmatic diapsid Paliguana whitei and the early history of Lepidosauromorpha. Issue 1957 (25th August 2021) - Ford, David P.; Evans, Susan E.; Choiniere, Jonah N.; Fernandez, Vincent; Benson, Roger B. J.
Abstract : Lepidosaurs include lizards, snakes, amphisbaenians and the tuatara, comprising a highly speciose evolutionary radiation with widely varying anatomical traits. Their stem-lineage originated by the late middle Permian 259 million years ago, but its early fossil record is poorly documented, obscuring the origins of key anatomical and functional traits of the group. Paliguana whitei, from the Early Triassic of South Africa, is an enigmatic fossil species with the potential to provide information on this. However, its anatomy and phylogenetic affinities remain highly uncertain, and have been debated since its discovery more than 100 years ago. We present microtomographic three-dimensional imaging of the cranial anatomy of P. whitei that clarifies these uncertainties, providing strong evidence for lepidosauromorph affinities based on the structure of the temporal region and the implantation of marginal dentition. Phylogenetic analysis including these new data recovers Paliguana as the earliest known stem-lepidosaur, within a long-lived group of early diverging lepidosauromorphs that persisted to at least the Middle Jurassic. Our results provide insights into cranial evolution on the lepidosaur stem-lineage, confirming that characteristics of pleurodont dental implantation evolved early on the lepidosaur stem-lineage. By contrast, key functional traits related to hearing (quadrate conch) and feeding (streptostyly) evolved later in the lepidosaur crown-group.